Perception of Asthma as a Factor in Career Choice among Young Adults with Asthma - Sacha Bhinder; Lisa Cicutto; Husam M Abdel-Qadir; Susan M Tarlo (Canadian Respiratory Journal)
BACKGROUND/AIM: Asthma is a common chronic condition that can be aggravated by workplace exposures. Young adults with asthma should know how their future occupation might affect their asthma, and potentially, their quality of life. The aim of the present study was to assess the awareness of young adults to occupational risks for asthma and high-risk occupations, as well as their perception of the role of asthma in career choice.